A Fast in-Motion Alignment Algorithm for DVL Aided SINS. (4th June 2014) - Kang, Li; Ye, Lingyun; Song, Kaichen
Abstract : Doppler velocity log (DVL) aided strapdown inertial navigation system (SINS) is a common navigation method for underwater applications. Owing to the in-motion condition and the lack of the GPS, it is a challenge to align a SINS under water. This paper proposed a complete in-motion alignment solution for both attitude and position. The velocity update equation and its integral form in the body frame are studied, and the attitude coarse alignment becomes an optimization-based attitude determination problem between the body frame velocity and the integral form of gravity. The body frame velocity and the Earth frame position are separately treated, and the position alignment problem turns into an equation solving problem. Simulation and on-lake tests are carried out to examine the algorithm. The heading could reach around 10 deg accuracy and the pitch and roll could be aligned up to 0.05 deg in 60 s. With attitude error of this level, the heading could reach 1 deg accuracy in 240 s using unscented Kalman filter (UKF) based fine alignment. The final position error could achieve 1.5% of the voyage distance. This scheme can also be applied to other body frame velocity aided SINS alignments.